The Big Dark - Philbrick, W. R. (W. Rodman) (New York, New York : The Blue Sky Press, 2016)
When something knocks out everything electrical at midnight on New Years Eve, the world is plunged into chaos, including the town of Harmony, New Hampshire, where Webster Bragg, a vicious survivalist, sees an opportunity to dominate his fellow citizens--but as the town struggles to maintain order and civilization, young Charlie Cobb sets out on a dangerous journey through the snow to find medicine for his diabetic mother.
Keywords: Electric power failures -- Juvenile fiction; Survival -- Juvenile fiction; Families -- New Hampshire; Juvenile fiction; Survivalism -- Juvenile fiction; Adventure stories; Electric power failures -- Fiction; Survival -- Fiction; Family life -- New Hampshire; Fiction; Adventure and adventurers -- Fiction; New Hampshire -- Juvenile fiction; New Hampshire -- Fiction